The role of the internet in the secondary prevention of eating disorders - Clifton, EAD (2014)
The role of the internet in the secondary prevention of eating disordersEating disorders are a collection of serious mental illnesses. They are common causes of psychiatric morbidity amongst adolescent and young adult women and result in substantial costs to individuals, carers, communities, and health care services. Although evidence-based treatments are available, they fail to reach the majority of sufferers. Individuals often delay seeking help as a result of: shame, embarrassment, fear of stigma, an attendant desire to conceal the disorder, and low mental health literacy. Failure to recognise eating disorders in primary care settings, a shortage of therapists trained to provide individual face-to-face psychotherapy, and long waiting-lists may further delay the receipt of care. The present thesis set out to determine whether internet-delivered self-help might have the potential reduce this delay and to provide information to guide search engine optimisation for such interventions. It was comprised of two studies. Both involved the completion of a self-administered online questionnaire followed by a telephone discussion. The first recruited participants with a past or present eating disorder diagnosis who had previously taken part in a treatment trial. The second recruited participants through the website of a UK-based eating disorder’s charity. The studies indicated that, in the majority of cases, there was a substantial delay between the onset of an eating disorder and help-seeking. During this time, most individuals went online to seek help or information and would have considered using online self-help. Frequently used search terms were: 'eating disorders', 'anorexia', 'bulimia', and 'weight'. Those who experienced binge eating also often searched for 'binge eat'. The results suggest that the provision of an online secondary prevention self-help resource would be likely to bring forward the receipt of care. Such programs require the results of research, including the present thesis, to ensure that they are encountered by sufferers of eating disorders in their online searches.